Systemic paracoccidioidomycosis in a patient with enzymatic myeloperoxidase deficiency and acute lymphoblastic leukemia: case report - Sebastián Hoyos; Cristián Camilo Agudelo; Diana Mercedes Lozano; Luis Eduardo Buitrago (Bulletin of the National Research Centre, 2022)
Abstract Background Paracoccidioidomycosis is a systemic fungal infection that is potentially fatal, and the most prevalent of its kind in Latin America. The predisposition to infection appears to be related to abnormalities in cellular immunity, given its low prevalence in endemic regions. The role of myeloperoxidase deficiency has not been elucidated. Case presentation We present a case of 48-year-old female patient with acute lymphoblastic leukemia, stem cell transplant candidate, who developed a fever with lymphadenopathy and lung nodules, consistent with paracoccidioidomycosis infection, in whom a myeloperoxidase deficiency was later discovered. The treatment of the hematologic malignancy had a good impact solving the enzymatic deficiency and antifungal therapy achieve controlling the infection. Conclusions This case lays out the possible association between acute leukemia, an alteration in neutrophil function (needed to fight fungal infections) and an infection due to Paracoccidioides brasiliensis.